Illumination of exciton migration in rodlike luminescent conjugated polymers by single-molecule spectroscopy - Wang, C.; White, J.; Lim, T.; Hsu, J.; Yang, S.; Fann, W.; Peng, K.; Chen, S. (2003)
Single-molecule spectroscopy is used to study the time-dependent spectral behavior of a short rodlike Poly(phenylene vinylene) (PPV) derivative polymer spin cast in a polystyrene matrix. The fluorescent time trace is characterized by stepwise intensity emission with constant spectral composition, punctuated by abrupt intensity changes, which are usually accompanied by abrupt spectral changes. In contrast to coiled long chain polymers, defect-free rodlike polymers exhibit multiple-emission sites, each with its characteristic invariant spectrum. The distribution of spectral jumps in the emission spectrum reflects the distribution of the effective conjugation length. This implies the energy transfer (i.e., thermalized exciton migration) along the polymer backbone is inefficient. A static disorder induced conjugation length distribution model with limited energy transfer can be used in understanding the photophysics of an isolated polymer.